1998
DOI: 10.1046/j.1471-4159.1998.71062439.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Prevents Experimental Parkinsonism in Rodents and Induces Striatal Increase of Neurotrophic Factors

Abstract: The repeated finding of an apparent protective effect of cigarette smoking on the risk of Parkinson's disease is one of the few consistent results in the epidemiology of this disorder. Among the numerous substances that originate from tobacco smoke, nicotine is by far the most widely studied. Nicotine is a natural alkaloid that has considerable stimulatory effects on the CNS. Its effects on the CNS are mediated by the activation of neuronal heteromeric acetylcholine‐gated ion channel receptors (nAChRs, also te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
1
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(118 citation statements)
references
References 29 publications
7
107
1
3
Order By: Relevance
“…In vivo, chronic nicotine treatment can rescue dopaminergic cell bodies in substantia nigra (Janson and Moller, 1993) and nerve terminals in striatum (Fuxe et al, 1990) from mechanical lesion, restore glucose utilization in lesioned areas (Owman et al, 1989), counteract lesion-induced dopamine receptor up-regulation (Janson et al, 1994), and increase dopamine turnover rate (Fuxe et al, 1990). In addition, both acute and chronic nicotine treatment in vivo can protect the nigrostriatal system from lesion by the selective neurotoxins MPTP, methamphetamine, or 6-hydroxydopamine (Janson et al, 1992;Maggio et al, 1998;Costa et al, 2001;Parain et al, 2001;Ryan et al, 2001), although chronic infusion of high-dose nicotine using an osmotic minipump increases MPTP-mediated toxicity (Behmand and Harik, 1992;Janson et al, 1992;Hadjiconstantinou et al, 1994). Overall, the above studies, and studies showing that nicotine can rescue differentiated PC12 cells (Meyer et al, 1998a) and cultured spinal cord motoneurons (Messi et al, 1997;Garrido et al, 2000) from growth factor deprivation or arachidonic acid toxicity, suggest that nicotine is neuroprotective for a wide variety of neuronal types against many different toxic insults.…”
Section: Neuronal Nachrs and Neuroprotectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo, chronic nicotine treatment can rescue dopaminergic cell bodies in substantia nigra (Janson and Moller, 1993) and nerve terminals in striatum (Fuxe et al, 1990) from mechanical lesion, restore glucose utilization in lesioned areas (Owman et al, 1989), counteract lesion-induced dopamine receptor up-regulation (Janson et al, 1994), and increase dopamine turnover rate (Fuxe et al, 1990). In addition, both acute and chronic nicotine treatment in vivo can protect the nigrostriatal system from lesion by the selective neurotoxins MPTP, methamphetamine, or 6-hydroxydopamine (Janson et al, 1992;Maggio et al, 1998;Costa et al, 2001;Parain et al, 2001;Ryan et al, 2001), although chronic infusion of high-dose nicotine using an osmotic minipump increases MPTP-mediated toxicity (Behmand and Harik, 1992;Janson et al, 1992;Hadjiconstantinou et al, 1994). Overall, the above studies, and studies showing that nicotine can rescue differentiated PC12 cells (Meyer et al, 1998a) and cultured spinal cord motoneurons (Messi et al, 1997;Garrido et al, 2000) from growth factor deprivation or arachidonic acid toxicity, suggest that nicotine is neuroprotective for a wide variety of neuronal types against many different toxic insults.…”
Section: Neuronal Nachrs and Neuroprotectionmentioning
confidence: 99%
“…A number of studies have shown that nicotine treatment can increase growth factor signaling. Nicotine can increase release of FGF-2 in the striatum, as well as levels of FGF-2 in many brain areas including neocortex, hippocampus, substantia nigra, and striatum (Maggio et al, 1997(Maggio et al, , 1998Belluardo et al, 1998). Brain-derived neurotrophic factor (BDNF) was also elevated in the striatum (Maggio et al, 1998).…”
Section: Potential Mechanisms Underlying Nachr-mediated Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse efeito protetor é corroborado pela literatura vigente 44 . Em modelo experimental de parkinsonismo em ratos, a nicotina apresentou-se como protetor neuronal por meio da indução de fatores neurotróficos 45 .…”
Section: Discussionunclassified
“…To this regard, we have shown the neuroprotective effects of nicotine in two models of PD, that is, MPTP-and methamphetamine-treated rats, by virtue of increased BDNF expression, thus implying modulation of the neurotrophin as a mechanism through which nicotine protects from experimental parkinsonism. 82 Support to this theory derives from French et al 83 as well as Kenny et al 84 who showed increased expression of hippocampal BDNF following both acute and chronic nicotine administration raising the possibility that nicotine might improve cognition, at least in part, by such a mechanism. These findings raise the interesting issue that nAChR-based pharmacological treatments may help the therapy of cognitive dysfunctions associated with PD.…”
Section: Nicotinementioning
confidence: 98%